2011
DOI: 10.1007/s12348-011-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase II placebo-controlled study of nepafenac ophthalmic suspension 0.1% for postoperative inflammation and ocular pain associated with cataract surgery in Japanese patients

Abstract: ObjectiveThis study aimed to examine the efficacy and safety of nepafenac ophthalmic suspension compared to placebo in the management of postoperative inflammation and ocular pain in Japanese patients undergoing cataract surgery.MethodsThis was a multicenter, randomized, double-masked, placebo-controlled clinical study. Patients received nepafenac or placebo TID beginning 1 day before cataract surgery and continuing on the day of surgery for 14 days. One additional drop was administered on the day of surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Both are effective in resolving postoperative inflammation and pain, increasing patient comfort, and decreasing the risk of complications [1, 711]. NSAIDs act through inhibition of cyclooxygenase enzymes, thereby blocking the production of prostaglandins [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both are effective in resolving postoperative inflammation and pain, increasing patient comfort, and decreasing the risk of complications [1, 711]. NSAIDs act through inhibition of cyclooxygenase enzymes, thereby blocking the production of prostaglandins [12].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs of increased prostaglandins production, except pain, include inflammation, which is classically treated with steroids and nonsteroidal anti-inflammatory drugs (NSAIDs) (Kohnen, 2015). Numaga et al found that 0.1% nepafenac seems to be a safe and efficacious ophthalmic suspension for postoperative inflammation and eye pain following cataract surgery or other ophthalmic procedures (Numaga et al, 2012). On the other hand, Ogurel et al evaluated analgesic effectiveness and patient satisfaction of 0.1% nepafenac in patients who underwent bilateral cataract surgery with VAS and VPS (Oğurel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the authors who used nepafenac in photorefractive keratectomy (PRK) and cataract surgery concluded that topical nepafenac was safe and effective to perform topical analgesia. [9][10][11][12] The control of pain originating from the cornea and/or conjunctiva is a problem for the patients undergoing surgeries related to ocular surface, such as pterygium surgery, refractive surgery, and strabismus surgery. There are many techniques and methods described for the management of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Nepafenac (Nevanac; Alcon, Turkey) has been used to control the pain after many ocular surgeries. [9][10][11][12] It is unique among ophthalmic NSAIDs in that it is a prodrug deaminated to amfenac, a highly effective nonselective COX inhibitor. 13 It has superior corneal permeability characteristics compared with other available topical NSAIDs that minimize surface complications often observed with topical NSAIDs 14 and has been proven to have an acceptably great margin of safety.…”
mentioning
confidence: 99%
See 1 more Smart Citation